Strategies applied by Ngoc Thu Lang in English-VietNamese translation of slang in “the godfather”= Chiến lược được Ngọc Thứ Lang áp dụng trong dịch Anh – Việt từ lóng trong tác phẩm « bố già » - Hoàng, Thị Thu Yên (2020)
Slang plays an important role in linguistic system and deserves greater attention. However, justified significance has not been attached to slangy vocabulary due to slang‟s features of vulgarism, in-group identification and inconsistency. Not only have studies dedicated to slang occupied a small percentage among scientific papers but most of them have also focused on linguistic aspects of slang. Translation in slang has not been received appropriate attention. These factors encouraged the researcher to carry out this paper with objectives of having a look at characteristics of slang and translation strategies applied in rendering slang. The novel “The Godfather” and its Vietnamese version translated by Ngoc Thu Lang were chosen as subjects of this study. Document analysis was adopted as the research method. Slang classification based on theories offered by Eble (1996) and Mattielo (2008) identified 9 common types of slang. 79 slang in the novel selected after a purposive sampling process revealed that 7 among 9 types of slang were detected. Regarding translation strategies, softening (Blonskyte and Petroniene, 2013) and compensation (Garcarz, 2011) were the most favorable strategies applied by translator Ngoc Thu Lang.